Speed and the Speed of Light, Density, Change, and Absolute Zero-Motion and Change in the Principles of the Philosophy of the Cosmic Origin (London Journal of Research In Science: Natural and Formal, 2026)
Speed is a physical or sociological term for the motion and change of matter — the distance traveled by matter per unit of time and the rate of change in the structural form of “existence” per unit of time. It relates to the three-dimensional spatial coordinate system and is a physical unit associated with time and space. It represents human-created physical knowledge and information that “materializes” space and time（Materialization，serving as a necessary condition for studying physics, the motion and change of matter, and as an important unit in the philosophy of matter and a key reference indicator in the philosophy of the cosmic origin.The existence and change of position and structure are necessary indicators in the philosophy of matter and physics, and serve as causal–logical reference indicators in the philosophy of the cosmic origin.Density is the physical unit of matter or energy’s existence in three-dimensional space — the amount of matter–energy–existence per unit volume. It relates to the three-dimensional spatial coordinate system and describes the structure and form of space and the existence within space. It is human-created knowledge and information resulting from “materializing” space, representing a necessary condition for studying physics and the existence of matter, an important indicator in the philosophy of matter, and a key reference in the philosophy of the cosmic origin. It is unrelated to time and describes only the structural form of existence.The speed of light and absolute zero are theoretical limits discovered in physics — units in Einstein’s theory of relativity, Kelvin’s “theory of absolute zero,” as well as optics, electromagnetics, quantum mechanics, and thermodynamics (Samo Liu, 2024i). They are important knowledge and information in the philosophy of the cosmic origin.
Keywords: change and speed; density; matter and non-matter; Motion; perception of existence; Physics; speed of light and absolute zero; structure and existence